Ammonia nitrogen adsorbent, application thereof and live fish transportation method
By using high-efficiency ammonia nitrogen adsorbent and fill column purification treatment technology, the problem of ammonia nitrogen accumulation in live fish transportation is solved, the survival rate and muscle quality of live fish are improved, and a safe and environmentally friendly transportation process is achieved.
Patent Information
- Application Number
- CN202510044671.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-12
- Publication Date
- 2025-03-21
AI Technical Summary
During the transportation of live fish, the ammonia nitrogen concentration in the water accumulates sharply, resulting in serious impact on the survival rate and muscle quality of live fish, and it is difficult for the existing technology to effectively control the ammonia nitrogen concentration.
It adopts a highly efficient ammonia nitrogen adsorbent made of materials such as straw biochar and magnesium chloride, which has high adsorption rate and renewability, and is purified by ammonia nitrogen through a filler column during transportation.
It effectively reduces the ammonia nitrogen concentration in the transport water, improves the survival rate and muscle quality of live fish, and reduces transportation costs, and is safe and environmentally friendly.
Smart Images

Figure CN119657084A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fresh product transportation, and particularly relates to an ammonia nitrogen adsorbent and an application thereof and a live fish transportation method. Background Art
[0002] During transportation, live fish will be subjected to environmental stress (crowding stress, ammonia nitrogen stress, and hypoxia stress, etc.), which will produce stress reactions. Usually, the muscle quality of fish after transportation stress deteriorates (water holding capacity decreases, shear force decreases, and color becomes pale), which in turn affects consumer acceptance. Factors that affect stress reactions during transportation include transportation temperature, dissolved oxygen in the water, ammonia nitrogen, vibration, etc. At present, the transportation of live fish in my country mainly relies on live fish transport vehicles equipped with oxygen tanks and refrigerated water tanks for transportation, which can better solve the problems of high temperature and low dissolved oxygen in the transportation water, so that the temperature and dissolved oxygen in the transportation water can be easily controlled within a range suitable for transportation. However, there are few reports on control measures for ammonia nitrogen concentration in water bodies.
[0003] The production of ammonia nitrogen in the transport water is mainly derived from the nitrogen excretion of the fish itself and the decomposition of its feces by microorganisms. In this regard, some scholars have found that the fish are usually treated with temporary rearing before transportation. During the temporary rearing stage, the fish can fully discharge the excrement in the body, reduce metabolism and oxygen consumption, and slow down the accumulation of ammonia nitrogen. However, the temporary rearing time for the best muscle quality of the fish during the temporary rearing process is still unclear. In addition, the applicant's research found that temporary rearing can only reduce the source of ammonia nitrogen in the feces during subsequent transportation, but cannot reduce the nitrogen excretion of the live fish itself. In addition, in the transportation of live fish, in order to reduce transportation costs and improve transportation efficiency, the transportation density of live fish is usually large, and the transportation time is also long. Under this transportation condition, the ammonia nitrogen in the transport water accumulates sharply, which can be increased from 0.16mg / L to about 50mg / L, thereby seriously affecting the survival rate and muscle quality of live fish during live fish transportation. Summary of the invention
[0004] In view of the above problems, the present invention provides an ammonia nitrogen adsorbent and its application and a live fish transportation method.
[0005] The present invention is achieved through the following technical solutions.
[0006] In the first aspect, the present invention provides a high-efficiency ammonia nitrogen adsorbent, characterized in that the carbon content of the ammonia nitrogen adsorbent is 59%-61%, the oxygen content is 29%-31%, the nitrogen content is 7%-8%, the magnesium content is 1%-1.2%, and the porosity is 0.30-0.35cm 3 / g, average pore size of 7.2-7.3nm, specific surface area of 260-268m 2 / g; the ammonia nitrogen adsorption rate of the ammonia nitrogen adsorbent in the simulated water body with an initial ammonia nitrogen concentration of 50 mg / L is greater than 80%; the ammonia nitrogen adsorption rate of the ammonia nitrogen adsorbent in the transport water body during the transportation of live fish is 33%-53%.
[0007] Specifically, the preparation method of the ammonia nitrogen adsorbent is:
[0008] S1. After the straw biochar and magnesium chloride solution are fully mixed, they are placed in a 40°C magnetic stirrer and stirred continuously for 10-15 hours. Then the stirring is stopped and sealed with a sealing film and immersed for 10-15 hours. After that, the solution is filtered and the filter residue is dried to obtain magnesium-loaded straw biochar powder;
[0009] S2. Add chitosan powder with a viscosity of 200-400 mPa·s to glacial acetic acid, place it in a magnetic stirrer, and stir continuously at a temperature of 40°C until a gel is uniformly formed, then add the magnesium-loaded straw biochar powder obtained in step S2, continue stirring to form a uniform solid-liquid mixture gel, and then slowly drop the solid-liquid mixture gel into a 1 mol / L NaOH precipitation tank to form gel microspheres, and then filter and wash it repeatedly with distilled water for several times, and then place it in 2% glutaraldehyde for 24 hours; finally, wash the fixed gel microspheres in distilled water for several times until the pH is neutral, place it in a 105°C oven to dry, seal it with a vacuum packaging machine, and store it in a desiccator to obtain the ammonia nitrogen adsorbent of the present invention.
[0010] Preferably, in step S1, the mass volume ratio of the straw biochar to the magnesium chloride solution is 1:10 g / mL, and the molar concentration of the magnesium chloride solution is 2 mol / L; in step S2, the mass volume ratio of the chitosan to the glacial acetic acid is 1:50 g / mL, and the mass concentration of the glacial acetic acid is 2%; the mass ratio of the magnesium-loaded straw biochar powder to the chitosan is 2:1.
[0011] In a second aspect, the present invention provides the use of the above-mentioned ammonia nitrogen adsorbent in the transportation of live fish.
[0012] Specifically, the application method is: using an ammonia nitrogen adsorbent to adsorb ammonia nitrogen in water during the transportation of live fish, so as to improve the survival rate and muscle quality of the live fish.
[0013] In a third aspect, the present invention provides a method for long-term and high-density live fish transportation, characterized in that it comprises the following steps:
[0014] (1) Temporary holding treatment: live fish to be transported are placed in a micro-flow water temporary holding pond, the mass ratio of live fish to temporary holding water is controlled to be 1:25-35, the temporary holding time is 1-4 days, 3% α-ketoglutaric acid is added to the temporary holding water at the beginning of the temporary holding, and the temporary holding water is continuously replaced with groundwater as the water source during the temporary holding period;
[0015] (2) Transport of live fish: After temporary rearing, the live fish are transferred to a transport box of a transport vehicle for transportation, and the mass ratio of live fish to transport water is controlled to be 1:1-1:3. The transportation time is 12-24 hours, and the transport water is purified from ammonia nitrogen during transportation. The specific method of ammonia nitrogen purification is to set a filling column on the outside of the transport box, fill the filling column with the ammonia nitrogen adsorbent described in claim 1, and during transportation, the transport water is pumped out from the top of the transport box and sent into the filling column, and the ammonia nitrogen in the transport water is adsorbed by the ammonia nitrogen adsorbent, and then the transport water is pumped back to the bottom of the transport box.
[0016] Preferably, in the temporary curing treatment of step (1), the temporary curing time is 2-3 days, and the amount of α-ketoglutaric acid added is 3%.
[0017] Preferably, during the transport of live fish in step (2), the ammonia nitrogen purification treatment is carried out intermittently, that is, the ammonia nitrogen purification treatment is stopped for 15-30 minutes after every 3-8 minutes; oxygenation treatment is carried out during the period when the ammonia nitrogen purification treatment is stopped, and the oxygenation treatment is specifically, oxygen is introduced from the bottom of the transport water body by aeration, and the oxygen introduction amount per 100kg of live fish is controlled to be 600-800 ml / hour.
[0018] Preferably, the ammonia nitrogen adsorbent particles are filled in layers in a filling column, filter cotton is filled between adjacent ammonia nitrogen adsorbent particle layers, and an isolation layer is set at the top of the uppermost ammonia nitrogen adsorbent particle layer and the bottom of the lowermost ammonia nitrogen adsorbent particle layer, and the isolation layer is composed of a double layer of wire mesh with filter cloth in the middle.
[0019] Preferably, during the ammonia nitrogen purification process, when the ammonia nitrogen adsorbent particles are saturated with adsorption, they are subjected to analytical treatment and regenerated for use.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The present invention obtains an ammonia nitrogen adsorbent in the form of hydrogel particles by cross-linking and modifying deacetylated chitosan, which not only improves its adsorption performance, but also facilitates its practical application and makes the material immobilized, which is beneficial to the adsorption process.
[0022] (2) The ammonia nitrogen adsorption material prepared by the present invention can be used under low temperature conditions, has a strong ammonia nitrogen adsorption effect, is renewable, has a low preparation cost, and is safe and environmentally friendly.
[0023] (3) The present invention uses an external ammonia nitrogen adsorbent to circulate and extract the transport water during the transportation process, and uses the ammonia nitrogen adsorbent to adsorb the ammonia nitrogen in the transport water, which can prevent the ammonia nitrogen adsorbent from being directly added to the transport water and affecting the activity of live fish. At the same time, the filter cotton, the isolation layer and the ammonia nitrogen adsorbent are used for layered filling, which increases the contact cotton knots between the ammonia nitrogen adsorbent and the water body, making it easy to load and recycle. The water flow is usually not easy to be blocked, and the feces, mucus and pollutants in the water body can be better intercepted.
[0024] (4) The present invention reduces the discharge of fish feces during transportation by temporarily raising the fish, and the α-ketoglutaric acid in the water can help inhibit the generation of ammonia in the fish, thereby reducing nitrogen emissions, thereby reducing the nitrogen excretion of the fish itself during transportation.
[0025] (5) The ammonia nitrogen purification treatment of the present invention is carried out in an intermittent manner, which can prevent the ammonia nitrogen purification treatment from interfering with the conventional oxygenation treatment, and is beneficial to improving the survival rate of live fish transportation. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a diagram showing the adsorption effects of different ammonia nitrogen adsorption materials on the market on ammonia nitrogen in water.
[0027] Figure 2 This is a diagram showing the adsorption effect of magnesium-loaded straw biochar powder and magnetic iron-loaded straw biochar powder on ammonia nitrogen in water.
[0028] Figure 3 This is a diagram showing the effect of magnesium-loaded biochar powder and modified magnesium-loaded straw biochar powder on the adsorption of ammonia nitrogen in water.
[0029] Figure 4 This is a diagram showing the adsorption effect of different powder particle sizes, microsphere diameters and water addition amounts on ammonia nitrogen in water.
[0030] Figure 5 It is the nitrogen adsorption and desorption curve diagram of different ammonia nitrogen adsorption materials;
[0031] Figure 6 This is the pore size diagram of different ammonia nitrogen adsorption materials;
[0032] Figure 7 The scanning electron microscope images of different ammonia nitrogen adsorption materials;
[0033] Figure 8 XRD patterns of different ammonia nitrogen adsorption materials;
[0034] Fig. 9 FTIR images of different ammonia nitrogen adsorption materials;
[0035] Fig.10 The pseudo-first-order and second-order kinetic model fitting diagrams of different ammonia nitrogen adsorption materials;
[0036] Fig.11 This is the intra-particle diffusion model diagram of different ammonia nitrogen adsorption materials;
[0037] Fig.12 This is the isothermal adsorption model diagram of different ammonia nitrogen adsorption materials;
[0038] Fig.13 The results of the reusability test of the ammonia nitrogen adsorption material were evaluated for three adsorption-desorption cycles;
[0039] Fig.14 This is the effect of ammonia nitrogen adsorbent on the survival rate and muscle quality of live fish during actual transportation;
[0040] Fig.15 This is a schematic diagram of using the ammonia nitrogen adsorbent of the present invention to transport live fish;
[0041] Fig.16 for Fig.15 A magnified schematic diagram of the local structure. DETAILED DESCRIPTION
[0042] The embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals represent the same or similar elements or elements having the same or similar functions from beginning to end. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the embodiments of the present invention, and cannot be understood as limiting the embodiments of the present invention.
[0043] Example 1
[0044] Determination of substrate for preparation of ammonia nitrogen adsorbent.
[0045] 1. Experimental methods
[0046] The straw biochar, wood activated carbon, ceramic balls, nano-hydroxyapatite, and new copper-based modified MOFs materials purchased on the market were selected as the substrates of ammonia nitrogen adsorbents, and the ammonia nitrogen adsorption rates of the above substrates on simulated water bodies were determined. The specific determination method is as follows: 5g of straw biochar, wood activated carbon, ceramic balls, nano-hydroxyapatite, and new copper-based modified MOFs materials were weighed respectively, added to a 150mL conical flask, and then 50mL of ammonia nitrogen solution with an initial ammonia nitrogen concentration of 50mg / L was added, and the conical flask was sealed with plastic wrap and placed in a constant temperature oscillator. The oscillator temperature was set at 13 °C and the oscillator speed was set at 120 r / min. Samples were taken at 0, 10, 30, 60, 90, 240, 360, 540, 720, 1320, and 1440 min, respectively. The samples were taken out and centrifuged at 5000 r / min for 10 min. The samples were filtered using a 0.45 μm microporous membrane. The changes in the ammonia nitrogen concentration in the simulated water were determined using an ammonia nitrogen meter, and the ammonia nitrogen adsorption rate was calculated. The ammonia nitrogen adsorption rate is the ratio of the change in the ammonia nitrogen concentration in the simulated water to the initial ammonia nitrogen concentration in the simulated water. The determination results are shown in Figure 1 .
[0047] 2. Experimental results
[0048] from Figure 1 It can be seen that different ammonia nitrogen adsorption materials show significant differences, among which straw biochar powder has the best ammonia nitrogen adsorption effect, followed by wood activated carbon powder. Adsorption equilibrium is reached at about 720 minutes. However, ceramic balls, nanohydroxyapatite and new copper-based modified MOFs materials have poor adsorption effects on ammonia nitrogen at low temperatures. The ammonia nitrogen adsorption rate of straw biochar powder on simulated water is about 16%.
[0049] Example 2
[0050] Determination of modification method of ammonia nitrogen adsorbent.
[0051] 1. Experimental methods
[0052] Taking into account the cost of practical application, improving the adsorption performance and recyclability of the powder, and according to the measurement results of Example 1, we selected straw biochar as the substrate for modification, and compared the following two modification methods, as follows:
[0053] (1) Magnesium loading treatment is performed by immersing the powder in a magnesium chloride solution. Weigh 10 g of straw biochar powder and 100 mL of 2 mol / L magnesium chloride, mix thoroughly, place in a magnetic stirrer, stir at 40 °C for 12 h, then stop stirring and seal with a sealing film and immerse for 12 h, then filter the solution, take the filter residue and dry it in an oven at 105 °C to obtain magnesium-loaded straw biochar powder;
[0054] (2) The powder was immersed in a ferric chloride solution for iron loading. 10 g of straw biochar powder was weighed and mixed with 100 mL of 2 mol / L ferric chloride solution, and then placed in a magnetic stirrer and stirred at 40 °C for 12 h. Then the stirring was stopped and sealed with a sealing film and immersed for 12 h. After that, the solution was filtered and the filter residue was placed in an oven at 105 °C for drying to obtain magnetic iron-loaded straw biopowder.
[0055] The ammonia nitrogen adsorption rate of the two modified substrates on the simulated water body was determined. The specific determination method is as follows: 0.4g of the prepared magnesium-loaded biochar powder and magnetic iron-loaded biochar powder were weighed and added into 150mL conical flasks respectively, and then 50mL of ammonia nitrogen solution with an initial ammonia nitrogen concentration of 50mg / L was added. The conical flask was sealed with plastic wrap and placed in a constant temperature oscillator. The oscillator temperature was set to 13°C and the oscillator speed was set to 120r / min. Samples were taken at 0, 10, 30, 60, 90, 240, 360, 540, 720, 1320, and 1440min respectively. The samples were taken out and centrifuged at 5000r / min for 10min, filtered with a 0.45μm microporous membrane, and the changes in ammonia nitrogen concentration in the simulated water were determined by an ammonia nitrogen meter, and the ammonia nitrogen adsorption rate was calculated. The ammonia nitrogen adsorption rate is the ratio of the change in ammonia nitrogen concentration in the simulated water body to the initial ammonia nitrogen concentration in the simulated water body. The determination results are shown in Figure 2 .
[0056] 2. Experimental results
[0057] from Figure 2 It can be seen that with the extension of time, the concentration of ammonia nitrogen in the simulated water body decreased significantly after adding magnesium-loaded straw biochar powder and magnetic iron-loaded straw biochar powder. However, the adsorption performance of magnesium-loaded straw biochar powder is higher than that of magnetic iron-loaded straw biochar powder.
[0058] Example 3
[0059] Optimization of adsorption capacity of ammonia nitrogen adsorbent.
[0060] 1. Experimental methods
[0061] Taking into account the cost of practical application, further improving the adsorption performance and recyclability of the powder, and based on the measurement results of Example 2, we selected the magnesium-loaded straw biochar powder in Example 2 for further modification, and the modification method is as follows:
[0062] 1 g of chitosan with a viscosity of 200-400 mPa·s was added to 50 mL of 2% glacial acetic acid, placed in a magnetic stirrer, and stirred continuously at a temperature of 40°C until a gel was uniformly formed. Then, 2 g of the magnesium-loaded straw biochar powder prepared in Example 2 was added, and stirring was continued to form a uniform solid-liquid mixture gel. The solid was injected into a 5 mL syringe and slowly dripped into a 1 mol / L NaOH precipitation tank to form gel microspheres. The solid was then filtered and washed repeatedly with distilled water for several times, and then placed in 2% glutaraldehyde for fixation for 24 h. Finally, the fixed gel microspheres were washed several times in distilled water until the pH was neutral, placed in a 105°C oven for drying, sealed with a vacuum packaging machine, and stored in a desiccator to obtain modified magnesium-loaded straw biochar powder, i.e., the ammonia nitrogen adsorbent of the present invention.
[0063] The ammonia nitrogen adsorption rate of the modified magnesium-loaded straw biochar powder obtained after further modification on the simulated water body was determined. The specific determination method was as follows: 0.4 g of the prepared modified magnesium-loaded straw biochar powder (ammonia nitrogen adsorbent of the present invention) and the magnesium-loaded straw biochar powder of Example 2 were weighed and added into 150 mL conical flasks respectively, and then 50 mL of an ammonia nitrogen aqueous solution with an initial ammonia nitrogen concentration of 50 mg / L was added, the conical flask was sealed with plastic wrap and placed in a constant temperature oscillator, the oscillator temperature was set to 13 ° C, and the oscillation was continued for 2 hours. The speed of the device was 120 r / min. Samples were taken at 0, 10, 30, 60, 90, 240, 360, 540, 720, 1320, and 1440 min, respectively. The samples were taken out and centrifuged at 5000 r / min for 10 min. The samples were filtered using a 0.45 μm microporous membrane. The changes in the ammonia nitrogen concentration in the simulated water were determined using an ammonia nitrogen meter, and the ammonia nitrogen adsorption rate was calculated. The ammonia nitrogen adsorption rate is the ratio of the change in the ammonia nitrogen concentration in the simulated water to the initial ammonia nitrogen concentration in the simulated water. The determination results are shown in Figure 3 .
[0064] 2. Experimental results
[0065] Depend on Figure 3 It can be seen that after the simulated water body with an initial ammonia nitrogen concentration of 50 mg / L was treated with modified magnesium-loaded straw biochar powder and magnesium-loaded biochar powder adsorption, the ammonia nitrogen concentration in the simulated water body of the magnesium-loaded biochar powder group was reduced to 42 mg / L, and the ammonia nitrogen concentration in the simulated water body of the modified magnesium-loaded straw biochar powder group was reduced to 8 mg / L. Therefore, the adsorption performance of the magnesium-loaded straw biochar powder was greatly improved after modification in this embodiment. According to calculations, in a simulated water body with an initial ammonia nitrogen concentration of 50 mg / L, the ammonia nitrogen adsorbent obtained by further modification in this embodiment can achieve an adsorption rate of more than 80% for ammonia nitrogen in the simulated water body.
[0066] Example 4
[0067] Based on the experimental studies of Example 1, Example 2 and Example 3, this example provides a method for preparing the ammonia nitrogen adsorbent of the present invention, and the specific steps are as follows:
[0068] S1. 10 g of straw biochar was fully mixed with 100 mL of 2 mol / L magnesium chloride and placed in a magnetic stirrer. The mixture was stirred at 40 °C for 12 h. The stirring was then stopped and sealed with a sealing film and immersed for 12 h. The solution was then filtered and the residue was dried in an oven at 105 °C to obtain magnesium-loaded straw biochar powder.
[0069] S2. Add 1 g of chitosan powder with a viscosity of 200-400 mPa·s to 50 mL of 2% glacial acetic acid, place it in a magnetic stirrer, and stir continuously at a temperature of 40°C until a gel is uniformly formed. Then, add 2 g of magnesium-loaded straw biochar powder prepared in Example 2, continue stirring to form a uniform solid-liquid mixture gel, inject it into a 5 mL syringe and slowly drip it into a 1 mol / L NaOH precipitation tank to form gel microspheres, and then filter and wash it repeatedly with distilled water for several times, and then place it in 2% glutaraldehyde for 24 hours; finally, wash the fixed gel microspheres in distilled water several times until the pH is neutral, place it in a 105°C oven to dry, seal it with a vacuum packaging machine, and store it in a desiccator to obtain the ammonia nitrogen adsorbent of the present invention.
[0070] After testing, the carbon content of the ammonia nitrogen adsorbent provided in this embodiment is 59%-61%, the oxygen content is 29%-31%, the nitrogen content is 7%-8%, the magnesium content is 1%-1.2%, and the porosity is 0.30-0.35cm 3 / g, average pore size of 7.2-7.3nm, specific surface area of 260-268m 2 / g, the ammonia nitrogen adsorption rate of the ammonia nitrogen adsorbent provided in this embodiment in the simulated water body with an ammonia nitrogen concentration of 50 mg / L is greater than 80%, and the ammonia nitrogen adsorption rate of the transport water body during the transportation of live fish is 33%-53%.
[0071] Example 5
[0072] Based on the preparation method of the ammonia nitrogen adsorbent of the present invention determined in Example 4, this example studies the particle size of the magnesium-loaded straw biochar powder, the diameter of the ammonia nitrogen adsorbent of the present invention, and the addition amount of the ammonia nitrogen adsorbent of the present invention, and the specific parameters are set as follows:
[0073]
[0074] The experimental results are as follows Figure 4 As shown by Figure 4It can be seen that the particle size of magnesium-loaded straw biochar powder is 3278nm, and the ammonia nitrogen adsorbent has better adsorption performance when the diameter is 2mm. As the amount of ammonia nitrogen adsorbent added to water increases, the amount of ammonia nitrogen adsorbed in water also increases, but the increase is not large. Considering the cost of actual production application, the amount of ammonia nitrogen adsorbent added is selected to be 8g / L.
[0075] Example 6
[0076] Structural characterization of the ammonia nitrogen adsorbent of the present invention.
[0077] 1 Experimental methods
[0078] 1.1 Experimental subjects
[0079] The ammonia nitrogen adsorbent prepared in Example 4 was used as an experimental object, and compared with other commonly used ammonia nitrogen adsorption materials on the market, straw biochar, magnesium-loaded straw biochar, chitosan microspheres, and chitosan straw biochar microspheres;
[0080] 1.2 Specific surface area and pore size distribution analysis (BET)
[0081] Adsorbent preparation conditions: The experimental object was dried in an oven (105°C), ground into powder, and then subjected to BET characterization. Nitrogen adsorption-desorption test refers to the test of the specific surface area and pore size distribution of the material. This study used the BK300C instrument produced in Beijing. The main operation is: at an operating temperature of 77K, gas N2 is adsorbed to obtain the adsorption-desorption isotherm curve. The Brunaure-Emmet-Teller (BET) method is usually used to calculate the specific surface area of the sample, and the Barrett-Joyner-Halenda (BJH) method is selected to calculate the pore size distribution of the sample.
[0082] 1.3 Scanning electron microscopy analysis (SEM) and elemental composition analysis (EDS)
[0083] Field emission scanning electron microscope was used to observe the surface morphology, pore structure, etc. at a certain magnification. The element composition and distribution of the material were determined by energy dispersive spectrometer (EDS).
[0084] 1.4 X-ray diffraction analysis (XRD)
[0085] The graphitization degree of biochar was tested using an X-ray diffractometer D8 Advance. Test conditions: scanning range (2θ) 5°~80°; scanning speed 5°min -1 .
[0086] 1.5 Infrared spectroscopy analysis (FTIR)
[0087] The functional groups of activated carbon were characterized by infrared spectrometer. The raw material was ground into powder with potassium bromide at a ratio of 1:100 and pressed into tablets for testing. Test conditions: Test range 400~4000cm -1 , scan times 64 times, spectral resolution 4cm -1 .
[0088] 2. Experimental results
[0089] Table 1 Elemental composition and pore structure parameters of ammonia nitrogen adsorption materials
[0090]
[0091] Nitrogen adsorption and desorption curves and pore size distribution of different ammonia nitrogen adsorption materials Figure 5 and 6 As shown, the specific surface area of the sample is calculated by using the BET method, and the pore size distribution of the sample is calculated by the BJH method. The calculated porosity and average pore size results are shown in Table 1. The microstructure, elemental composition, diffraction peaks, and characteristic functional groups of different ammonia nitrogen materials were observed by SEM, EDS, XRD, and FTIR.
[0092] Adsorption-desorption curves and average pore size distribution of different ammonia nitrogen adsorbent materials Figure 5 and Figure 6 As shown. According to the IPUAC classification of nitrogen adsorption and desorption isotherms (Ballou and Doolen), we found that the hysteresis loops in straw biochar, magnesium-loaded straw biochar, chitosan straw biochar microspheres and the ammonia nitrogen adsorbent of the present invention belong to type IV isotherms with H4 hysteresis loops. No adsorption limitation is shown in the high pressure range (P / Po≈1). This phenomenon is consistent with the structural characteristics of biochar, while chitosan microspheres do not appear, indicating that there is no obvious nonlinear relationship between the adsorption amount and the relative pressure (p / p0). Table 1 lists the pore structure parameters (specific surface area, porosity, average pore size) of straw biochar, magnesium-loaded straw biochar, chitosan microspheres, chitosan straw biochar microspheres and the ammonia nitrogen adsorbent of the present invention. Among them, the specific surface area of straw biochar, magnesium-loaded straw biochar, chitosan straw biochar microspheres and the ammonia nitrogen adsorbent of the present invention is 267-955m 2 / g, the average pore size distribution curve is relatively wide, mainly distributed between 2 and 58 nm, indicating that they are all mesoporous materials. The specific surface area of deacetylated chitosan microspheres is only 0.51 m 2 / g, and its porosity and average pore size were not detected. This is also consistent with its microstructure, such as Figure 7As shown in Table 1, no pore structure was observed in the chitosan microspheres. However, uniform pore structures appeared in other structures, and the surface of the straw biochar modified with magnesium loading was the roughest and had a large pore size. As shown in Table 1, through elemental composition analysis, we found that magnesium can be loaded in straw biochar by impregnation, and the ratio of N element increased significantly after modification with chitosan.
[0093] like Figure 8 As shown, the straw biochar powder mainly has diffraction peaks at 2θ=25° and 43°, and its diffraction peak intensity is weak. The diffraction peaks of the straw biochar after magnesium impregnation are still mainly these two, but the peak intensity is significantly increased. Unlike these two materials, chitosan microspheres have diffraction peaks at 2θ=20° and 35°. After chitosan modification, the X-ray diffraction structure of chitosan-loaded magnesium biochar microspheres is different from other structures. Its diffraction peaks increase, mainly distributed at 2θ=20°, 40° and 60°. FTIR results show that chitosan microspheres contain rich characteristic functional groups, such as Fig. 9 As shown, there are hydroxyl, carboxyl, carbon oxygen bond, carbon hydrogen bond and nitrogen hydrogen bond, etc. Other ammonia nitrogen adsorbent materials have fewer characteristic functional groups, such as carboxyl, hydroxyl and magnesium oxygen bond functional groups in the ammonia nitrogen adsorbent of the present invention.
[0094] Example 7
[0095] Adsorption characteristics of different ammonia nitrogen adsorption materials.
[0096] 1. Experimental methods
[0097] 1.1 Experimental subjects
[0098] The ammonia nitrogen adsorbent prepared in Example 4 was used as an experimental object, and compared with other commonly used ammonia nitrogen adsorption materials on the market, straw biochar, magnesium-loaded straw biochar, chitosan microspheres, and chitosan biochar microspheres;
[0099] 1.2 Adsorption kinetics
[0100] Weigh 0.4g of straw biochar, magnesium-loaded straw biochar, deacetylated chitin microspheres, chitin straw biochar microspheres and the ammonia nitrogen adsorbent of the present invention, add them into a 150mL conical flask, add 50mL of ammonia nitrogen aqueous solution with an initial ammonia nitrogen concentration of 50mg / L, seal the conical flask with plastic wrap and put it into a constant temperature oscillator, set the oscillator temperature to 13°C, the oscillator speed to 120r / min, take samples at 0, 10, 30, 60, 90, 240, 360, 540, 720, 1320, 1440min, take out the samples and centrifuge them at 5000r / min for 10min, filter them with a 0.45μm microporous membrane, use an ammonia nitrogen meter to measure the changes in ammonia nitrogen concentration in the simulated water body, and use the pseudo-first-order kinetic equation, pseudo-second-order kinetic equation and intraparticle diffusion equation for fitting. The equations of the three kinetic models are expressed as follows:
[0101] Pseudo-first-order kinetic model:
[0102]
[0103] Pseudo-second-order kinetic model:
[0104]
[0105] Particle Diffusion Model:
[0106] Q t =K i t 1 / 2 + C i (3)
[0107] Where Q e and Q t are the adsorption amount of ammonia nitrogen on the adsorbent at equilibrium and at different times (mg / g); K1 (min -1 ) and K2(g·mg -1 ·min -1 ) are the rate constants for first-order and second-order kinetics; K i is the intraparticle diffusion rate constant (mg·g -1 ·min -0.5 ), C i (mg / g) is a constant representing the thickness of the boundary layer film.
[0108] 1.3 Adsorption isotherm
[0109] Weigh 0.4g of straw biochar, magnesium-loaded straw biochar, chitosan microspheres, chitosan straw biochar microspheres, and chitosan magnesium-loaded straw biomicrospheres, add them into a 150mL conical flask, and then add 50mL of ammonia nitrogen aqueous solution with initial ammonia nitrogen concentrations of 5, 20, 50, 100, and 200mg / L. Seal the conical flask with plastic wrap and put it into a constant temperature oscillator. Set the oscillator temperature to 13°C and the oscillator speed to 120r / min. After oscillating for 24h, take out the sample and centrifuge it at 5000r / min for 10min, filter it with a 0.45μm microporous filter membrane, and use an ammonia nitrogen meter to determine the changes in ammonia nitrogen concentration in the simulated water body. Use the Langmuir model, Freundlich model, and Temkin model for fitting. The equations of the three isothermal adsorption models are expressed as follows:
[0110] Langmuir Model:
[0111]
[0112] Freundlich Model
[0113]
[0114] Temkin Model
[0115] Q e = BlnA + BlnC e (6)
[0116] C e is the mass concentration of ammonia nitrogen in the solution at adsorption equilibrium (mg / L); Q e Equilibrium adsorption capacity of ammonia nitrogen (mg / g); Q m is the maximum adsorption capacity obtained by fitting (mg / g); K L is the Langmuir constant (related to adsorption energy) (L·mg -1 );K F is the Freundlich constant, which is related to the adsorption capacity and adsorption intensity respectively; A=K T , K T is the Temkin constant; B = RT / b; R is the universal gas constant (8.314 J / mol·K); T is the absolute temperature (K); and b is the change in adsorption energy in the Temkin model.
[0117] 2. Experimental results
[0118] Table 2 Kinetic model equation parameters
[0119]
[0120] In order to explore the adsorption performance of the above materials on ammonia nitrogen, the pseudo-first-order kinetic equation and the pseudo-second-order kinetic equation were used to fit the adsorption process of straw biochar, magnesium-loaded straw biochar, chitosan microspheres, chitosan biochar microspheres, and the ammonia nitrogen adsorbent of the present invention. Fig.10 It can be seen that each ammonia nitrogen adsorption material has significant adsorption in the first few minutes of the reaction, and the adsorption rate is fast. The adsorption rate of straw biochar, magnesium-loaded straw biochar, chitosan microspheres, chitosan biochar microspheres and the ammonia nitrogen adsorbent of the present invention gradually decreases after about 720, 540, 1320, 720, and 1440 minutes, respectively, until the adsorption equilibrium is reached. Table 2 is the parameters of the kinetic model equation. From the fitting results, it can be seen that the pseudo-first-order kinetics R of the ammonia nitrogen adsorption process 2 The values are all smaller than the R 2 The value indicates that the second-order kinetic equation can better simulate the ammonia nitrogen adsorption process. It also indicates that chemical adsorption is the main adsorption pathway. The adsorption amount of the ammonia nitrogen adsorbent of the present invention is the largest at the adsorption equilibrium, which is 5.58 mg / g.
[0121] Table 3 Parameters of intraparticle diffusion model equation
[0122]
[0123] from Fig.11 It can be seen that the fitting curve of the intraparticle diffusion model presents three linear stages. The adsorption rate in the first stage is very fast, which is an instantaneous external surface adsorption; the second stage is the intraparticle diffusion process, the adsorption rate is slow, and it is the rate-controlling step of the entire adsorption process; in the third stage, the adsorption reaches equilibrium. Table 3 lists the parameters of the intraparticle diffusion model for ammonia nitrogen adsorption on different materials. It can be seen from the data in the table that the correlation coefficient R between the first stage fitting curve and the second stage fitting curve in the adsorption process is 2 All are greater than 0.7, and the linear correlation is good. Among different materials, K1 is greater than K2 and K3, and C3 is greater than C2 and C1, which indicates that the adsorption rate in the first stage is greater than the adsorption rate in the second stage and greater than the adsorption rate in the third stage. The boundary layer formed in the second and third stages of the adsorption process is thicker than the boundary layer formed in the first stage, which is also the reason why the adsorption rate in the second and third stages slows down. From Table 2, we also found that the diffusion coefficient K2 in the mesopores and the diffusion coefficient K3 in the micropores of the ammonia nitrogen adsorbent of the present invention are significantly higher than those of other ammonia nitrogen adsorbent materials.
[0124] Table 4 Parameters of adsorption isotherm model equation at 13℃
[0125]
[0126] The adsorption isotherm models of ammonia nitrogen by different ammonia nitrogen adsorption materials are as follows: Fig.12As shown in Table 4, with the increase of the initial concentration of ammonia nitrogen in the simulated transport water, the adsorption amount also increases. This is because the ammonia nitrogen in contact with the adsorbent, magnesium ions and the simulated transport water may be more conducive to the adsorption of aqueous solutions with higher initial concentrations. The fitting parameters of the adsorption isotherm model are shown in Table 4. It can be seen from the table that the correlation coefficient R of the Temkin equation model for straw biochar and magnesium-loaded straw biochar is 2 is greater than the Freundlich model and the Langmuir model, indicating that the Temkin model can better simulate the adsorption process. It also shows that the adsorption of straw biochar and magnesium-loaded straw biochar can be explained as a multilayer adsorption and chemical adsorption process. The correlation coefficient R of the Langmuir equation model of chitosan microspheres, chitosan biochar microspheres and the ammonia nitrogen adsorbent of the present invention is 2 It is greater than the Freundlich and Temkin models, indicating that the Langmuir model can better simulate the adsorption process. In addition, it also shows that the adsorption of ammonia nitrogen by chitosan microspheres, chitosan biochar microspheres and the ammonia nitrogen adsorbent of the present invention can be explained as a monolayer adsorption, in which ammonia nitrogen is evenly distributed on the surface of the microspheres and gradually reaches adsorption equilibrium.
[0127] Example 8
[0128] The regenerative property of the ammonia nitrogen adsorbent of the present invention was evaluated by three adsorption-desorption cycles, and compared with other recyclable ammonia nitrogen adsorbent materials on the market, namely, chitosan microspheres and chitosan straw biochar microspheres.
[0129] 1. Experimental methods
[0130] Weigh 0.4g of the ammonia nitrogen adsorbent of the present invention prepared in Example 4, add it to a 150mL conical flask, add 50mL of an ammonia nitrogen aqueous solution with an initial ammonia nitrogen concentration of 50mg / L, seal the conical flask with plastic wrap and put it into a constant temperature oscillator, set the oscillator temperature to 13°C, and the oscillator speed to 120r / min. When the adsorption reaches equilibrium, take out the sample and centrifuge it at 5000r / min for 10min, filter it with a 0.45μm microporous filter membrane, and use an ammonia nitrogen meter to determine the ammonia nitrogen concentration. After that, the ammonia nitrogen adsorbent was filtered out and placed in 1mol / L NaOH at an oscillation speed of 150r / min and a temperature of 25°C for 24h for analysis. After the experiment, the ammonia nitrogen adsorbent was placed in a 50°C oven for drying, and then the next ammonia nitrogen adsorption-analysis experiment was carried out, and a total of three adsorption-analysis cycles were carried out. The changes in ammonia nitrogen concentration during three adsorptions and analysis were measured using an ammonia nitrogen meter, and the ammonia nitrogen adsorption amount and ammonia nitrogen adsorption rate of the simulated water body were calculated. The results of the test are shown in Fig.13 .
[0131] 2. Experimental results
[0132] Depend on Fig.13 It can be seen that the ammonia nitrogen adsorption capacity of the ammonia nitrogen adsorbent of the present invention can reach 82.54%, which is much higher than that of other groups of materials. Generally, in addition to the adsorption capacity, the reusability of the adsorbent material is also a key factor in its application. Fig.13 It can be seen that after three desorptions, the ammonia nitrogen adsorbent of the present invention can still achieve a removal rate of 42.58% for ammonia nitrogen, which is still significantly higher than other groups. The results show that the ammonia nitrogen adsorbent of the present invention is a good ammonia nitrogen adsorbent that can be recycled.
[0133] Example 9
[0134] The application effect of the ammonia nitrogen adsorbent of the present invention in the transportation of live fish.
[0135] 1. Experimental materials
[0136] We selected the ammonia nitrogen adsorbent parameters determined in Example 5, that is, the particle size of the magnesium-loaded straw biochar powder was 3278nm, the diameter of the ammonia nitrogen adsorbent was 2mm, and the amount of ammonia nitrogen adsorbent added was 8g / L for the experiment to explore its application effect in live fish transportation.
[0137] 2. Experimental methods
[0138] 2.1 High-density transportation
[0139] Healthy and vigorous bighead bream of similar size were placed in plastic insulated boxes, 10 per group. The amount of water during transportation was twice the weight of the fish, and the amount of ammonia nitrogen adsorbent added by the present invention was 8 g / L. Ice bags were added during the experiment to maintain the temperature in the transport water at around 13°C. The plastic insulated box was then placed on a simulated transport platform (DK-5024, Xingsuo Intelligent Equipment Co., Ltd., Xiamen, China) to simulate the commercial bighead bream transportation process, and the vibration frequency was maintained at 120 rpm / min during the process. After 24 hours of simulated transportation, the transport water was taken for the determination of ammonia nitrogen concentration, and the back muscles were taken for testing muscle quality. Blank group: No ammonia nitrogen adsorbent of the present invention was added, and the other experimental parameters were the same as above.
[0140] 2.2 Single-cell keep-alive transport
[0141] The similar-sized, healthy and vigorous bighead bream are packaged in oxygenated fish bags, and the timing starts after the packaging is completed. The operation process is as follows: before packaging, water must be added to the fish bag by adding 3 times the volume of water by weight. The addition amount of the ammonia nitrogen adsorbent of the present invention is 8g / L, and the experiment is carried out after packaging in tea packaging bags. The packaging specification is 1 tail / bag. After exhausting the air in the fish bag, the fish bag is encapsulated and oxygenated, and then the sealed and oxygenated fish bag is placed in a foam insulation box. Then the foam insulation box is placed on a simulated transportation platform (DK-5024, Xingsuo Intelligent Equipment Co., Ltd., Xiamen, China) to simulate the commercial transportation process of bighead bream. After 24 hours of simulated transportation, the transportation water is taken to determine the ammonia nitrogen concentration, and the back muscle is taken to test the muscle quality. Blank group: No ammonia nitrogen adsorbent of the present invention is added, and the other experimental parameters are the same as above.
[0142] 3. Index determination
[0143] 3.1 Determination of ammonia nitrogen concentration: Take water samples from the treatment group and the blank group before and after simulated transportation, and use an ammonia nitrogen meter to determine the changes in ammonia nitrogen concentration in the water.
[0144] 3.2 Determination of survival rate: When the amblycephala completely loses its breath, it can be considered dead, with characteristics including floating head and white belly. When counting, each group of amblycephala was kept alive under the corresponding experimental conditions, and the statistical time points were 0h, 3h, 6h, 12h, 21h, and 24h after the start of keeping alive, and the number of each group still alive at each time point was counted.
[0145] The survival rate is calculated as:
[0146]
[0147] S t : survival rate of each group at different time; n t : The number of survivors in each group at different times; n: The initial number of each group, in this experiment, n is 10.
[0148] 3.3 Determination of muscle quality
[0149] Drip loss: Weigh 5 g of fish back muscle, hang it at 4℃ for 24 hours, then weigh the mass and calculate the drip loss.
[0150]
[0151] Where: M o is the starting mass, M i For the quality after completion
[0152] Shear force: The back muscles of the bighead bream were cut into 20 mm × 20 mm × 10 mm cuboids. The Wuchang fish pieces were cut perpendicular to the direction of the muscle fibers at a speed of 60 mm / min using a Japanese Taiyo Scientific Surimi Elasticity Tester (SD-700, Akiyama Technology Co., Ltd., Dongguan, China) equipped with a blade (15 mm in diameter). The shear force was recorded as the maximum force (g) during the measurement.
[0153] Chromaticity: The back meat of the bighead carp was cut into small pieces of 20 mm × 20 mm × 10 mm. A portable colorimeter (CR-400, Konica Minolta, Tokyo, Japan) was used to calibrate with a standard white plate before use, and L*, a*, and b* were recorded.
[0154]
[0155] Wherein: W represents the whiteness of the sample; L* value represents the brightness of the sample; a* value that is positive represents that the sample is reddish, while a* value that is negative represents that the sample is greenish; a b* value that is positive represents that the sample is yellowish, while a b* value that is negative represents that the sample is bluish.
[0156] 2. Experimental results
[0157] Fig.14 This is a graph showing the experimental results of the application effect of the ammonia nitrogen adsorbent of the present invention in the transportation of live fish. Fig.14 The results show that the survival rate of the ammonia nitrogen adsorbent of the present invention is significantly improved after the ammonia nitrogen adsorbent of the present invention is added to the ammonia nitrogen adsorbent of the present invention after high-density and single-body alive transportation. Among them, the survival rate of the ammonia nitrogen adsorbent of the present invention can reach 100% after single-body alive transportation for 24 hours, and the survival rate can still reach 80% after high-density transportation for 20 hours, which are significantly higher than the blank group. The ammonia nitrogen concentration also shows the same trend. After adding the ammonia nitrogen adsorbent of the present invention, the ammonia nitrogen concentration of the water body in both transportation modes after 24 hours of transportation is significantly reduced, as follows: the ammonia nitrogen concentration of the blank group of high-density transportation is 51.42 mg / L after 24 hours of transportation, and the treatment group is 34.38 mg / L. The ammonia nitrogen adsorption rate of the transported water body during high-density transportation is about 33%. The ammonia nitrogen concentration of the blank group of single-body alive transportation is 44.4 mg / L after 24 hours of transportation, and the treatment group is 20.72 mg / L. The ammonia nitrogen adsorption rate of the transported water body during single-body alive transportation is about 53%. In summary, the ammonia nitrogen adsorbent of the present invention has an adsorption rate of 33%-53% for ammonia nitrogen in the transport water during live fish transportation. After adding the ammonia nitrogen adsorbent of the present invention, the ammonia nitrogen in the transport water can be effectively adsorbed, thereby improving the survival rate of live fish during transportation.
[0158] Generally, the lower the drip loss rate of fish muscle, the lower the whiteness, brightness and redness of the muscle, and the higher the shear force, the better the quality of the fish muscle. After 24 hours of transportation, we measured the changes in the basic muscle quality of the amblycephala. Fig.14 The results showed that no matter it was single transport or high-density transport, after adding the ammonia nitrogen adsorbent of the present invention, the drip loss rate of the muscle of the bighead carp, the whiteness, brightness and redness values of the muscle were lower than those of the blank group, but the shear force did not change significantly, indicating that the addition of the ammonia nitrogen adsorbent of the present invention is beneficial to improving the quality of fish muscle during live fish transportation.
[0159] Example 9
[0160] Effects of temporary rearing on high-density live fish transportation.
[0161] 1. Experimental methods
[0162] Temporary holding treatment: Place the live fish to be transported in a micro-flow water temporary holding pond, control the mass ratio of live fish to temporary holding water to be 1:25, and the temporary holding time to be 1, 2, 3, or 4 days. Add 3% α-ketoglutaric acid to the temporary holding water, and use groundwater as the water source to continuously replace the temporary holding water during the temporary holding period.
[0163] 2. Index determination
[0164] Water holding capacity: Weigh about 3g of sample and wrap it with double-layer qualitative filter paper, centrifuge at 4000rpm for 15min. The water holding capacity is expressed as the ratio of the sample mass before and after centrifugation.
[0165] The methods for measuring shear force and chromaticity are the same as in Example 7.
[0166] 2. Experimental results
[0167] Table 5 Changes of ammonia nitrogen in transport water at different holding times and transport times
[0168]
[0169] Note: Capital letters indicate differences in the same column, and lowercase letters indicate differences in the same row.
[0170] Table 6 Effect of temporary rearing time on muscle quality of Megalobrama amblycephala
[0171] Temporary care time Water holding capacity (%) Shear force(g) L* a* b* W 0d 75.9±1.3C 300.36±59.77B 46.26±1.12A 0.98±0.46A -0.81±0.13BA 46.24±1.11A 1d 78.33±2.1B 375.97±83.97A 45.95±0.6BA 0.62±0.19B -1.01±0.18BA 45.94±0.6BA 2d 79.88±0.95A 407.11±82.6A 45.64±1.14BA 0.49±0.24B -0.98±0.51BA 45.63±1.13BA 3d 78.89±1.02BA 363.83±75.51A 45.86±1.24BA 0.57±0.23B -1.07±0.43B 45.84±1.23BA 4d 78.01±1.66B 355.61±60.21BA 45.08±1.22B 0.65±0.24B -0.72±0.18A 45.07±1.22B
[0172] As shown in Table 5, with the increase of transportation time, the ammonia nitrogen concentration in the transport water increased significantly. After 24 hours of transportation, the ammonia nitrogen concentration in the transport water of the group without temporary storage treatment reached 52.32 mg / L. After different time of temporary storage treatment, the ammonia nitrogen concentration in the transport water after 24 hours of transportation was 46.2-49.84 mg / L, which was significantly lower than that of the group without temporary storage treatment. As shown in Table 5, with the increase of temporary storage time, the water holding capacity and shear force in the muscle of Megalobrama amblycephala showed a trend of first increasing and then decreasing, and the redness value showed a trend of first decreasing and then increasing. Taking all factors into consideration, the best temporary storage time is 2-3 days.
[0173] Example 10
[0174] This embodiment provides a long-term and high-density live fish transportation method, which includes the following steps:
[0175] (1) Temporary holding treatment: live fish to be transported are placed in a micro-flow water temporary holding pond, the mass ratio of live fish to temporary holding water is controlled to be 1:25, the temporary holding time is 1 day, 3% α-ketoglutaric acid is added, and the temporary holding water is continuously replaced with groundwater as the water source during the temporary holding period;
[0176] (2) Live fish transportation: After temporary rearing, the live fish are transferred to the transport box of the transport vehicle 1 for transportation. The mass ratio of live fish to transport water is controlled to be 1:1. The transportation time is 24 hours. During the transportation, the transport water is purified by ammonia nitrogen treatment. Please refer to Fig.15 and Fig.16 The method for ammonia nitrogen purification treatment is to set a filling column 4 outside the transport box 2, fill the filling column 4 with the ammonia nitrogen adsorbent 5 prepared in Example 4, extract the transport water from the top of the transport box 2 and send it into the filling column 4 during transportation, use the ammonia nitrogen adsorbent to adsorb the ammonia nitrogen in the transport water, and then pump the transport water back to the bottom of the transport box 2; when the ammonia nitrogen adsorbent particles are saturated with adsorption, they are analyzed and regenerated for use; wherein, the ammonia nitrogen adsorbent 5 particles are layered and filled in the filling column 2, and the filter cotton 6 is filled between the adjacent ammonia nitrogen adsorbent 5 particle layers, wherein the number of layers of the ammonia nitrogen adsorbent 5 is 3-6 layers, and an isolation layer 7 is set at the top of the uppermost ammonia nitrogen adsorbent 5 particle layer and the bottom of the lowermost ammonia nitrogen adsorbent 5 particle layer, and the isolation layer 7 is composed of a double-layer wire mesh with a filter cloth in the middle. According to the test, under this transportation mode, the survival rate of live fish after the transportation is 78%.
[0177] Embodiment 11
[0178] The present embodiment provides a long-term and high-density live fish transportation method, the steps of which are the same as those of Example 10, except that the mass ratio of live fish to temporary holding water is 1:30, the temporary holding time is 3 days, the amount of α-ketoglutaric acid added is 3%, and the mass ratio of live fish to transportation water is 1:2; according to testing, under this transportation mode, the survival rate of live fish after the transportation is 79%.
[0179] Example 12
[0180] The present embodiment provides a long-term and high-density live fish transportation method, the steps of which are the same as those of Example 10, except that the mass ratio of live fish to temporary holding water is 1:35, the temporary holding time is 4 days, the amount of α-ketoglutaric acid added is 5%, and the mass ratio of live fish to transportation water is 1:3; after testing, under this transportation mode, the survival rate of live fish after the transportation is 81%.
[0181] Example 13
[0182] This embodiment provides a method for long-term high-density live fish transportation, and its steps and parameters are the same as those of embodiment 10, see Fig.15 and Fig.16 , the difference is that the ammonia nitrogen purification treatment is carried out in an intermittent manner, that is, the ammonia nitrogen purification treatment is stopped for 20 minutes after every 5 minutes; during the period when the ammonia nitrogen purification treatment is stopped, the oxygenation treatment is carried out, and the oxygenation treatment is specifically to use the aeration device 3 to introduce oxygen from the bottom of the transport water body by aeration, and the oxygen introduction amount per 100kg of live fish is controlled to be 600-800 ml / hour; after testing, under this transportation mode, the survival rate of live fish after transportation is 89%, which is significantly higher than the survival rate of live fish transportation in Example 11 and Example 12. It can be seen that the intermittent method of ammonia nitrogen purification can improve the survival rate of live fish.
Claims
1. A highly efficient ammonia nitrogen adsorbent, characterized in that: The ammonia nitrogen adsorbent has a carbon content of 59%-61%, an oxygen content of 29%-31%, a nitrogen content of 7%-8%, a magnesium content of 1%-1.2%, and a porosity of 0.30-0.35 cm 3 / g, average pore size of 7.2-7.3nm, specific surface area of 260-268m 2 / g; the ammonia nitrogen adsorption rate of the ammonia nitrogen adsorbent in the simulated water body with an initial ammonia nitrogen concentration of 50 mg / L is greater than 80%; the ammonia nitrogen adsorption rate of the ammonia nitrogen adsorbent in the transport water body during the transportation of live fish is 33%-53%.
2. The ammonia nitrogen adsorbent according to claim 1, characterized in that The preparation method of the ammonia nitrogen adsorbent is: S1. The straw biochar and magnesium chloride solution are fully mixed and placed in a 40°C magnetic stirrer for continuous stirring for 10-15 hours, and then the stirring is stopped and sealed with a sealing film for immersion for 10-15 hours. After that, the solution is filtered and the filter residue is dried to obtain magnesium-loaded straw biochar powder; S2. Add chitosan with a viscosity of 200-400 mPa·s to glacial acetic acid, place it in a magnetic stirrer, and stir continuously at a temperature of 40°C until a gel is uniformly formed, then add the magnesium-loaded straw biochar powder obtained in step S2, continue stirring to form a uniform solid-liquid mixture gel, and then slowly drop the solid-liquid mixture gel into a 1 mol / L NaOH precipitation tank with a syringe to form gel microspheres, and then filter and wash it repeatedly with distilled water for several times, and then place it in 2% glutaraldehyde for 24 hours; finally, wash the fixed gel microspheres in distilled water for several times until the pH is neutral, place it in a 105°C oven to dry, seal it with a vacuum packaging machine, and store it in a desiccator to obtain the ammonia nitrogen adsorbent of the present invention.
3. The ammonia nitrogen adsorbent according to claim 2, characterized in that In the step S1, the mass volume ratio of the straw biochar to the magnesium chloride solution is 1:10 g / mL, and the molar concentration of the magnesium chloride solution is 2 mol / L; in the step S2, the mass volume ratio of the chitosan to the glacial acetic acid is 1:50 g / mL, and the mass concentration of the glacial acetic acid is 2%; the mass ratio of the magnesium-loaded straw biochar powder to the chitosan is 2:
1.
4. Use of the ammonia nitrogen adsorbent according to claim 1 in the transportation of live fish.
5. The use according to claim 4, characterized in that Ammonia nitrogen adsorbents are used to absorb ammonia nitrogen in the water during the transportation of live fish to improve the survival rate and muscle quality of the live fish.
6. A method for long-term high-density live fish transportation, characterized in that: The steps include: (1) Temporary holding treatment: live fish to be transported are placed in a micro-flow water temporary holding pond, the mass ratio of live fish to temporary holding water is controlled to be 1:25-35, the temporary holding time is 1-4 days, 3% α-ketoglutaric acid is added to the temporary holding water at the beginning of the temporary holding, and the temporary holding water is continuously replaced with groundwater as the water source during the temporary holding period; (2) Transport of live fish: After temporary rearing, the live fish are transferred to a transport box of a transport vehicle for transportation, and the mass ratio of live fish to transport water is controlled to be 1:1-1:
3. The transportation time is 12-24 hours, and the transport water is purified from ammonia nitrogen during transportation. The specific method of ammonia nitrogen purification is to set a filling column on the outside of the transport box, fill the filling column with the ammonia nitrogen adsorbent described in claim 1, and during transportation, the transport water is pumped out from the top of the transport box and sent into the filling column, and the ammonia nitrogen in the transport water is adsorbed by the ammonia nitrogen adsorbent, and then the transport water is pumped back to the bottom of the transport box.
7. A long-term high-density live fish transportation method as claimed in claim 6, characterized in that: In the temporary curing treatment of step (1), the temporary curing time is 2-3 days, and the amount of α-ketoglutaric acid added is 3%.
8. A long-term and high-density live fish transportation method as claimed in claim 6, characterized in that: In the step (2) of transporting live fish, the ammonia nitrogen purification treatment is carried out intermittently, that is, the ammonia nitrogen purification treatment is stopped for 15-30 minutes after every 3-8 minutes; oxygenation treatment is carried out during the period when the ammonia nitrogen purification treatment is stopped. Specifically, the oxygenation treatment is to introduce oxygen from the bottom of the transport water body by aeration, and the oxygen introduction amount per 100kg of live fish is controlled to be 600-800 ml / hour.
9. A long-term high-density live fish transportation method as claimed in claim 6, characterized in that: The ammonia nitrogen adsorbent particles are filled in layers in the filling column, filter cotton is filled between adjacent ammonia nitrogen adsorbent particle layers, and an isolation layer is set at the top of the uppermost ammonia nitrogen adsorbent particle layer and the bottom of the lowermost ammonia nitrogen adsorbent particle layer. The isolation layer is composed of a double layer of wire mesh with filter cloth in the middle.
10. A long-term high-density live fish transportation method as claimed in claim 6, characterized in that: During the ammonia nitrogen purification process, when the ammonia nitrogen adsorbent particles are saturated with adsorption, they are subjected to analytical treatment and regeneration.